RANCANGAN PAKET AFTER SALES SERVICE SEBAGAI ALTERNATIF UPAYA PENINGKATAN PENJUALAN TOYOTA INNOVA DAN FORTUNER DI AUTO 2000 HR. MUHAMMAD SURABAYA - Gavin Tjandra Laksana; Joni Dewanto (Petra Christian University, 2015)
AUTO 2000 HR. Muhammad Surabaya which is engaged in the sale of automobiles and sparepart for the community. In the development of its car sales, suggesting that year-over-year salesdecline, especially cars Toyota Innova and Fortuner. The final task was created with the aim tofind and implement the right strategy, so that can increase sales, so as to face competition inworld car sales. Based on the literature study and apprenticeship process conducted by theauthor, due to the Sales Division is not maximized in achieving the targets set, the mediacampaign that has not been optimal use, and existing customers have not been faithful in thepurchase of a second or services offered by AUTO 2000 HR. Muhammad Surabaya. To that end,the author offers some solutions: 1) to provide sales and service for the Toyota Innova andFortuner through technical design in the form of packets, calculating and creative, so thatcustomers and prospective customers can see the benefits before and after the purchase ofvehicles; 2) conduct marketing communications through selected media such as posters,banners, x-banners, brochures, flyers, social media timeline, merchandise, and discountvouchers are applied in every event that took place.